Advancing urban resilience with modular construction: An integrated sustainability assessment framework - Mohammad Kamali; Kasun Hewage; Anber Rana; Shahria Alam; Rehan Sadiq (Resilient Cities and Structures, 2025)
Given the rapid growth of sustainable construction strategies globally and the importance of resiliency in civil infrastructure, it is crucial to adopt best practices. Modular construction is one such practice and is considered a better alternative to conventional construction in terms of resilience, construction times, resource efficiency, and sustainability. However, the continued expansion of modular construction relies on quantifying and evaluating its sustainability and the purported benefits. This paper develops and checks feasibility through an integrated multi-level decision support framework to empirically evaluate the sustainability performances of single-family residential modular homes. Criteria and indicator development and calculation, benchmark scale establishment, quantitative and qualitative data collection from literature and surveys, and multi-criteria decision analysis are unique aspects of this framework. The results of the two case studies located in the Okanagan region, Canada showed that modular homes perform at a higher level of sustainability than their conventional counterparts across multiple metrics and levels related to environmental and economic factors. The modular homes scored eco-efficiency values of 62.5 and 56.0, respectively and fell into higher performance range. The proposed framework offers flexibility in examining different dimensions of sustainability, providing valuable insights into the key parameters that need to be addressed to enhance overall sustainability. This research, which integrates life cycle thinking and decision-making, helps the construction industry and, municipalities, governments, and policymakers in making informed decisions on the selection of suitable construction methods in city developments and move towards a more resilient and sustainable sector.